Solving the economic dispatch problem with tabu search algorithm - Khamsawang, S.; Boonseng, C.; Pothiya, S. (My University, 2002)
The application of Tabu Search Algorithm (TSA) technique to solve Economic Dispatch problem (ED) with non-smooth fuel cost function is reported in this paper. Results from MATLAB on Pentium III-500 MHz system for three case studies are presented. Effectiveness of method was compared with many conventional methods. Result shows that the proposed method can provide accurate solution with rapid convergence time and has the potential to be applied to other power engineering problem.
Keywords: Economic dispatch; Tabu search algorithm